Physical and mechanical properties of some hybrid corn varieties - Ozturk, Turgut; Esen, Bilge (International Journal of Agricultural and Biological Engineering, 2013)
The aim of this study was to determine the structural designing parameters of silo and bins used for storage of some hybrid corn varieties (Zea mays L.). In the research, three corn varieties